2005
DOI: 10.1136/jme.2005.012302
|View full text |Cite
|
Sign up to set email alerts
|

Brief report on the experience of using proxy consent for incapacitated adults

Abstract: The Medicines for Human Use (Clinical Trials) Regulations 2004, which came into force in the UK in May 2004, cover the conduct of clinical trials on medicinal products. They allow a legal representative (a person not connected with the conduct of the trial) to consent to the participation of incompetent adults in medical research. Currently, very little is known about how such representatives will make their decisions. We have experience with proxy consent for older adults in a large, national trial. From 2445… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 8 publications
3
27
0
Order By: Relevance
“…The need for consent also affected the number of patients recruited; with an average of 1.5 per month when consent was necessary compared to 2 per month when it was not. This appears to substantiate the concerns raised by Mason et al [15].…”
Section: The Uk Situationsupporting
confidence: 66%
See 1 more Smart Citation
“…The need for consent also affected the number of patients recruited; with an average of 1.5 per month when consent was necessary compared to 2 per month when it was not. This appears to substantiate the concerns raised by Mason et al [15].…”
Section: The Uk Situationsupporting
confidence: 66%
“…Mason et al reported their experiences of recruiting incapacitated adults to the PRESSURE trial, which was investigating the best pressure relieving mattress for preventing pressure sores [15]. Incapacitated, and therefore immobile, patients are vulnerable to pressure sores, so were a group to whom the results would particularly apply.…”
Section: The Uk Situationmentioning
confidence: 97%
“…Nonetheless, this was an increase on our pilot study. Such participation rates are not rare in ICU research [20,23,24,36,37], especially for complex questionnaires on vignettes. This is undoubtedly due to patients' considerable residual fatigue and other impairments after recent ICU stays (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mason et al [14] investigated the effectiveness of pressure-relieving mattresses for use with older, frail patients, a study involving minimal risk to patients. They found that only 18% of those patients who possessed capacity refused consent compared to a 45% refusal rate from proxies for those patients who required proxy consent.…”
Section: Proxy Consentmentioning
confidence: 99%